2006
DOI: 10.1016/j.cub.2005.11.073
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Endosome-Associated Ubiquitin Isopeptidase AMSH by STAM, a Component of the Multivesicular Body-Sorting Machinery

Abstract: AMSH is an endosomal ubiquitin isopeptidase that can limit EGF receptor downregulation . It directly binds to the SH3 domain of STAM, which is constitutively associated with Hrs, a component of clathrin-coated structures on endosomes. This clathrin coat has been implicated in the recruitment of ubiquitinated growth factor receptors prior to their incorporation into internal vesicles of the multivesicular body (MVB) , through the concerted action of ESCRT complexes I, II, and III . We now show that AMSH is embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
187
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(198 citation statements)
references
References 21 publications
11
187
0
Order By: Relevance
“…As was expected from its high homology to yeast Vps24p, CHMP3 is now known to be a mammalian ESCRT-III subunit (Howard et al, 2001). Our present conclusion that AMSH binds CHMP3 is consistent with reports by others (Agromayor and Martin-Serrano, 2006;McCullough et al, 2006), and similar binding has been identified between Drosophila orthologues of these molecules (Giot et al, 2003). Although genetic evidence has already proven that ESCRT-III functions downstream of ESCRT-II in sorting and concentrating the ubiquitinated cargo of the MVB/late endosome (Bowers et al, 2004), the involvement of a DUB in mammalian MVB sorting had not been clarified previously.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…As was expected from its high homology to yeast Vps24p, CHMP3 is now known to be a mammalian ESCRT-III subunit (Howard et al, 2001). Our present conclusion that AMSH binds CHMP3 is consistent with reports by others (Agromayor and Martin-Serrano, 2006;McCullough et al, 2006), and similar binding has been identified between Drosophila orthologues of these molecules (Giot et al, 2003). Although genetic evidence has already proven that ESCRT-III functions downstream of ESCRT-II in sorting and concentrating the ubiquitinated cargo of the MVB/late endosome (Bowers et al, 2004), the involvement of a DUB in mammalian MVB sorting had not been clarified previously.…”
Section: Discussionsupporting
confidence: 92%
“…1D). Because earlier reports indicated that AMSH 1-103 , which includes the MIT-like domain (AMSH 34-97 ), is required for CHMP3 binding (McCullough et al, 2006;Tsang et al, 2006), our present study has further refined the responsible region. However, we found that the localization of AMSH to endosomes does not depend on the CHMP3 association (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations